Privacy, Hiding, Silencing, and Self-Revelation: A Conversation Between Steven Kuchuck and Steff Oates. (October 2016) - Oates, Steff; Kuchuck, Steven
When inviting contributors for this theme issue of the Transactional Analysis Journal, the coeditors recalled a webinar presented by Steven Kuchuck about the book Clinical Implications of the Psychoanalyst's Life Experience: When the Personal Becomes Professional. The book, which he edited and contributed to, speaks to much of what the guest coeditors had in mind for this journal and inspired their call for papers. Steven Kuchuck generously responded to their invitation to be involved in a dialogue about the book, which was carried out by guest coeditor Steff Oates.